KEDUDUKAN OBJEK JAMINAN KEBENDAAN DENGAN KEPEMILIKAN ATAS NAMA PIHAK KETIGA DALAM PROSES KEPAILITAN: Studi Putusan Nomor 08/Pdt.Sus GLL/2019/PN.Niaga.Jkt.Pst - Septia Salikhah Utami, (2023)
The provision of material guarantees by third party can lead to struggles between curators and creditors in carrying out the execution of collateral objects in the bankruptcy, as is the case with Decision Number 08/Pdt.Sus GLL/2019/PN.Niaga.Jkt.Pst. This research brings several formulations of the problem, namely how is the position of the object of material guarantees on behalf of third party and how is the ratio decidendi analysis of the panel of judges in Decision Number 08/Pdt.Sus-GLL/2019/PN.Niaga.Jkt.Pst which includes objects of material guarantees for names of third party into bankruptcy assets. This research is a normative juridical research with statutory and case approaches. The data obtained comes from secondary data and tertiary data in the form of interviews collected by literature study to be analyzed descriptively qualitatively. The results of the study show that referring to Article 1 point 1 in conjunction with Article 21 of the Bankruptcy Law, the position of the collateral object with ownership on behalf of a third party does not include bankrupt assets even though material guarantees have been charged to these assets so that the ratio decidendi of the panel of judges in deciding lawsuit No. 08/Pdt.Sus- GLL/2019/PN.Niaga.Jkt.Pst has been mistaken.